Analisis dan Mitigasi Risiko Pada Supply Chain di PT XYZ Dengan Pendekatan House of Risk (HOR) - Liddin, Jundana Shidqiyah; Pulansari, Farida (Universitas Al Azhar Indonesia, 2024)
In carrying out business processes in the LRT manufacturing sector, risks were discovered which resulted in disruption of the supply chain process in mitigating risks in the wiring harness supply chain. Risks are essentially events that have a negative impact on the Company's targets and strategies. Research data was collected by interviewing 3 respondents who were active employees of PT XYZ. Data processing uses the House of Risk (HOR) phase 1 and House of Risk (HOR) phase 2 models, and also uses several treatments such as determining the risk agent carried out by the handler and based on the highest Aggregate Risk Potential (ARP) priority value from the Pareto diagram. The results of this study show that there are 25 risk events caused by 33 causes of risk in the company's supply chain activities. Based on the Pareto diagram analysis, 80.85% priority mitigation actions were taken, of which 13 risk agents were proposed to minimize the most dominant risk causes.Keywords – Supply Chain, Risk Mitigation, House of Risk.